Ingroup solidarity drives social media engagement after political crises - Malia Marks; Yara Kyrychenko; Johan Gärdebo; Jon Roozenbeek (Proceedings of the National Academy of Sciences, 2025)
Social media are often said to exacerbate polarization by platforming hostility between groups. However, positive social emotions like ingroup solidarity may also drive social media engagement, particularly after major threats such as military invasions or terror attacks. In this preregistered study, we examine the socioemotional drivers of engagement following group threats in the context of the US 2024 presidential campaign trail, where both major political parties faced crises in July of 2024. We test how ingroup solidarity and outgroup hostility predicted social media users’ engagement with 62,118 posts by 484 US partisan accounts before and after the first Trump assassination attempt (July 13) and Biden’s re-election campaign suspension (July 21). We find that, while outgroup hostility is typically the dominant predictor of engagement, interactions with ingroup solidarity surged among Republicans after the Trump shooting and among Democrats after Biden’s withdrawal. We show that negativity toward other groups is not always key to going viral. Rather, positive ingroup emotions appear to play a leading role in times of crisis.